Retórica en arquitectura sustentable : el caso de la vivienda en Argentina (2010-2020) - Sánchez Crespo, Denise (2022)
The current investigation aims to study Argentinian sustainable households during the last decade (2010-2020) linking sustainable architecture with design perspective and argumentative rhetoric.\nIn order to question and conceptualize the notion of sustainable architecture, which has been widely spread and used at a rhetorical and discursive level in the last two decades (despite having few systematic theoretical bases in the architectural field) and with the purpose of finding a specific methodology for the discipline, three houses that exemplify the local sustainability will be analysed: Casa G, Refugio los Hipotálamos and Susurros del Viento.\nThis research paper will prove that it is possible to create a type of architecture with less environmental impact, which, by taking into account the context in which it is built, efficiently solves dwelling problems, while, at the same time and through mixed communicational strategies, informs of its benefits: both from the form itself as well as external to it. During this investigation, it will be pointed out that the awareness regarding sustainable designs has been growing, however, until now, it has not become an ethical purpose for architects (Hernandez-Pezzi, 2010); Hence, this thesis aims to contribute to the rethinking of the current way of producing, communicating and criticizing the established paradigms, including the sustainability one.